PEMBAGIAN .WARIS .ADAT .SUKU .BUTON DALAM .PERSPEKTIF .HUKUM . .ISLAM (STUDI .KASUS . .DI .DESA .GUNUNG . .SEJUK - Muhamad Safar Juniaddin; Dwi Ari Kurniawati; Moh. Muslim (Jurnal Hikmatina, 2021)
The research in this paper departs from the curiosity of researchers about the heritage of the Burton tribe in Gunung Sejuk Village, Sampolawa District, South Burton Regency, which is predominantly Muslim. This is contrary to Islamic law in practice, namely that women and men get the same share (1:1), while in Islamic law it is regulated that men and women get a share (2:1) in inheritance. Based on this background, the researcher hopes to study the distribution of the traditional heritage of the Burton tribe in Gunung Sejuk Village, Samporawa District, South Burton Regency in terms of Islamic law. . .This .study .uses .a .qualitative .research .method .with .the .type .of .empirical .research. .Information .collection .techniques .in .this .study .using .purposive .sampling .technique .based .on .predetermined .criteria, .data .collection .using .in-depth .interviews .(in-dept .interviews) .and .documentation. .The .result .in .this .study, .distribution .of .traditional .legacy .from .the .Buton .tribe .in .the .perspective .of .Islamic .law .in .Gunung .Sejuk .Village, .Sampolawa .District, .South .Buton .Regency, .which .is .a .damaged .tradition .because .it .is .not .in .accordance .with .islamic .law. . .